Maximizing Organization Performance: The Role Of Travel Business In Jakarta? - Ian Nurpatria Suryawan (Jurnal Manajemen, 2022)
This research has the purpose to analyze the effect of competitive intensity, dynamic capability, organization slack and organization innovation on organization performance on travel business in Jakarta. The sampling method was carried out by researchers utilizing non-probability sampling with the number of questionnaires distributed randomly to 100 travel business owners. The results of this study show the results of testing 4 (four) hypotheses: competitive intensity has an effect on organization innovation, organizational slack has an effect on organization innovation, organization innovation has an influence on organization performance and dynamic capability has no influence on organizational innovation. This research has a novelty on competitive intensity, organization slack and organization innovation actually improve organization performance in tourism travel businesses in Jakarta. This study, making policies related to dynamic capability on organizational performance did not have the ability to seize opportunities and turn organizational resources into more productive.